Possible areas for molecular intervention for crop improvement in Hevea brasiliensis - theoretical considerations - Sethuraj M R (IRRDB symposium on physiological and molecular aspects of the breeding of Hevea brasiliensis 6-7 November 1995, 1995)
The last decade has seen worldwide efforts to use molecular biology methods to transform crop plants by introduction of agronomically desirable genes. In this new molecular approach, it has become possible to bring about specific plant genome changes by addition of one or more genes. In conventional breeding, entire sets of chromosomes are combined and desired parental genotypes are not necessarily reconstituted. The new approach offers the potential to make relatively quick and specific changes in elite cultivars without disrupting their otherwise desirable genotypic constitution. While highly attractive in concept with tremendous scientific potential, the generation of a transgenic crop plant is confronted with innumerable technical hurdles. The paper discusses progress to date and the opportunities for further progress in the future.
Keywords: AFLD; Crop improvement; Disease resistance; Drought tolerance; Genetic transformation; Hevea brasiliensis; Molecular biology; Molecular cloning; Molecular farming; RAPD; RFLP; TPD syndrome